Mathematical literacy ability on project based learning model with RME approach assisted by schoology - Asmara, Maharani; Wardono, Wardono (Department of Mathematics, Universitas Negeri Semarang, 2019)
Abstract Mathematical literacy skills need to be improved so that students are able to solve mathematical problems correctly. This study aims to (1) To find out the mathematical literacy abilities of students in the PjBL model with the RME approach assisted by media, Schoology can achieve classical completeness or more; (2) To find out which one is better between the average mathematical literacy abilities in the PjBL model, the RME approach is assisted by Schoology's media in the experimental class and the DL model's Scientific approach in the control class. The population in this study was VII grade students in a school in the city of Semarang. This research is quantitative research. Sampling is done by random sampling technique. The results of the study showed that using the PjBL model of the RME approach assisted by Schoology in achieving classical completeness, and learning the PjBL with the RME approach assisted by the Schoology media in the experimental class had an average mathematical literacy ability compared to DL learning Scientific approaches in the control class.